1986
DOI: 10.1302/0301-620x.68b4.3733825
|View full text |Cite
|
Sign up to set email alerts
|

Overgrowth of the femur after fracture in childhood. An increased effect in boys

Abstract: Forty-four children, treated conservatively for fracture of the shaft of a femur, were studied radiographically to assess the consequent increase in longitudinal growth of the bone. Overgrowth averaged 8.1 mm and was shown to be significantly greater in boys than in girls. Overgrowth did not appear to be influenced by the age of the patient, the type of injury, the type or site of the fracture, the amount ofoverlap of the fragments or by the handedness of the patient. OF THE FEMUR AFTER FRACTURE IN CHILDHOOD 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
2
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 4 publications
1
26
2
3
Order By: Relevance
“…Although femoral lengthening for congenital femoral deficiency has been described using a variety of techniques [4,31], to our knowledge, no data on the amount of length gained, ROM of the hip and knee, femoral growth inhibition or stimulation, patient-reported outcome scores, or specific complications have been reported using a single consistent technique. Inhibition of growth of the affected femur in congenital femoral deficiency is well known [3,8] as is the stimulation of growth after femur fracture [5,7,12,18,23,37,40,42]; however, the effect of limb lengthening on bone growth is controversial [17,34,38,45]. Lengthening surgery exerts tension on the soft tissues and pressure on the adjacent physis that may result in growth inhibition [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Although femoral lengthening for congenital femoral deficiency has been described using a variety of techniques [4,31], to our knowledge, no data on the amount of length gained, ROM of the hip and knee, femoral growth inhibition or stimulation, patient-reported outcome scores, or specific complications have been reported using a single consistent technique. Inhibition of growth of the affected femur in congenital femoral deficiency is well known [3,8] as is the stimulation of growth after femur fracture [5,7,12,18,23,37,40,42]; however, the effect of limb lengthening on bone growth is controversial [17,34,38,45]. Lengthening surgery exerts tension on the soft tissues and pressure on the adjacent physis that may result in growth inhibition [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon of overgrowth had been attributed by Speed 2 to a compensatory mechanism. Others regarded the increase to be due to hyperaemia associated with the healing process 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that bone fractures may stimulate longitudinal bone growth (Clement and Colton, 1986). In this study it was not possible to check for completely healed bone fractures.…”
Section: Discussionmentioning
confidence: 91%